Whoa.Nu: (Re)Constructing and Learning Swedish Hip-Hop Online - Ketil Thorgersen (MDPI AG, 2020)
Whoa.nu started in 2000 as a community where members discussed all aspects of hip-hop in Sweden. The community became the most important place not only for discussions among members but also for releasing free albums and songs to the public and for arranging events. Moreover, the site was an educational hub for members to learn about hip-hop. The core of Whoa.nu was the community, wherein the communicating environment of members developed as artists, audience, and critics. Whoa.nu was not only a place for individuals' learning processes and development but a place where Swedish hip-hop evolved and changed its regional frames, forming its own identity. The aim of this article was to present an analysis of the development of Whoa.nu as a learning platform for hip-hop in Sweden based on interviews with the two administrators of the site. Further, we wanted to use this as a steppingstone to discuss how listeners learned about popular music online during different eras. Two questions were at the forefront of this research: (1) How do the interviewees describe the internal views of the relation between how Whoa.nu and Swedish hip-hop changed over 13 years? and (2) how can Whoa.nu be understood as a learning environment? I henceforth present insights into how musical learning can happen outside of institutions and how Swedish hip-hop has grown from subculture to mainstream, which is how Whoa.nu outgrew itself. Hip-hop education is currently institutionalized in the same way that jazz and rock once were institutionalized. It went from being rebellious and subversive to being embraced by the larger society and integrated into academia. The results herein present a story of one example where musical learning in a subculture occurred. The insights presented, then, can help educators prepare for similar transformations of learning arenas in future musical subcultures. These insights could aid teachers and educators to assist students involved in music subcultures not discussed in schools. Hopefully, this article inspires additional ways of learning music.